Fibrin and Platelet-Rich Composition in Retrieved Thrombi Hallmarks Stroke With Active Cancer. Issue 12 (December 2020) - Fu, Chuan-Hsiu; Chen, Chih-Hao; Lin, Yen-Heng; Lee, Chung-Wei; Tsai, Li-Kai; Tang, Sung-Chun; Shun, Chia-Tung; Jeng, Jiann-Shing
Abstract : Background and Purpose: We aim to investigate whether histopathologic examination of thrombi retrieved from acute ischemic stroke patients undergoing endovascular treatment could distinguish cancer-related stroke from other etiologies. Methods: Thrombi from patients undergoing endovascular treatment were analyzed. The etiology of stroke was divided into cardioembolism, large artery atherosclerosis, and active cancer groups. All selected thrombi were subjected to hematoxylin and eosin staining. The percentages of fibrin/platelets, red blood cells, and white blood cells within a thrombus were quantified. Results: One-hundred fifty-two patients (active cancer, 19; cardioembolism, 107; large artery atherosclerosis, 26) were included. Thrombi from the active cancer group exhibited a higher fibrin/platelet composition than did those from the cardioembolism and large artery atherosclerosis groups (median, 85.7% versus 43.9% and 42.5%; P <0.001). Fibrin/platelet composition was the only independent factor (odds ratio, 1.05 [95% CI, 1.02–1.08]) in differentiating cancer-related stroke from stroke caused by cardioembolism and large artery atherosclerosis. A fibrin/platelet proportion of ≥65% accurately predicted cancer-related stroke (area under the curve, 0.84; P <0.001). Conclusions: In thrombi retrieved from patients undergoing endovascular treatment, a high fibrin/platelet composition was a probable indicator of cancer-related stroke. Abstract : Supplemental Digital Content is available in the text.